Brix/Acid Ratio as a Predictor of Consumer Acceptability of Crimson Seedless Table Grapes - Jayasena, Vijay; Cameron, J. (2008 Wiley Periodicals, Inc., 2008)
Harvesting at correct time is essential for the supply of quality grapes. There is no standard method to determine the proper time of harvesting for table grapes. The applicability of objective measurements such as soluble solids concentration (°Brix), acid contents (titratable acidity) and °Brix/acid ratio of Crimson Seedless table grapes were evaluated as predictors of quality in terms of consumer acceptability. Crimson Seedless table grapes were harvested from two locations in Western Australia at weekly intervals for 5 weeks. The samples were density sorted to get berries of different maturity levels. Objective measurements and sensory evaluation (panel of 63 judges) were conducted. There were significant (P less/equal 0.05) differences in the degree of liking among grapes of 16.0–17.0, 17.1–18.0 and 19.1–20.0°Brix. Consumer liking of grapes substantially changed with a change in acidity. The data revealed correlation coefficients of determination (r2) of 0.58, 0.79 and 0.85 between overall consumer acceptability and °Brix, acidity, and °Brix/acid ratio, respectively. °Brix/acid ratio was found to be the best objective measurement that reflected the consumer acceptability and can be used as a reliable tool to determine the optimum harvesting stage of Crimson Seedless table grapes.